If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 9 + -4 = 11x + 12 Reorder the terms: 9 + -4 + 6x = 11x + 12 Combine like terms: 9 + -4 = 5 5 + 6x = 11x + 12 Reorder the terms: 5 + 6x = 12 + 11x Solving 5 + 6x = 12 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 5 + 6x + -11x = 12 + 11x + -11x Combine like terms: 6x + -11x = -5x 5 + -5x = 12 + 11x + -11x Combine like terms: 11x + -11x = 0 5 + -5x = 12 + 0 5 + -5x = 12 Add '-5' to each side of the equation. 5 + -5 + -5x = 12 + -5 Combine like terms: 5 + -5 = 0 0 + -5x = 12 + -5 -5x = 12 + -5 Combine like terms: 12 + -5 = 7 -5x = 7 Divide each side by '-5'. x = -1.4 Simplifying x = -1.4
| 6p-2p=7 | | 4cos^3x=5cosx | | 2y(4x-6)=24 | | 10x-3=3x+13 | | -6y+9(5y+7)=7-5(1-y) | | 8x-1(6x+6)=8 | | 4x-30=-2x-6 | | x+2+4=4+4 | | 3z-3=2z+2 | | 7x-3(4x+8)=6x+12-9x | | 4x+22=7x+25 | | 3x^2+5x=-3 | | 6x+7x-57=38-6x | | 5(x-2)+11=6x-10 | | 31500-350x+90x-X^2=0 | | x^2+2x-11=-4x-4 | | (3y-2x+4)dx-(4x-3y-2)dy=0 | | 5(4h-7)=-18+6h | | 150=-0.8a+176 | | x^2+x+29=-9x+5 | | 16=-29k | | 2.5-0.03x=-1.19 | | .11x+29.99=35 | | 6.2x-5+x-2.1= | | -3(2b+4)+(7b-4)=0 | | 20m-12(m-3)=4 | | -29.99+0.11x=35 | | x^2-2-15=9 | | 2x-6+4x=42 | | -94=-8(2-r)+5r | | 7x^2+7x+10=0 | | -4=4+4v |